Determining Factors of Quality of Life in Tuberculosis Patients: A Qualitative Case Study in Yogyakarta - Liena Sofiana; Mateus Sakundarno Adi; Martini Martini; Mursid Raharjo (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The second-largest tuberculosis hotspot in the world is located in Indonesia, which creates a significant threat to global health. The disease causes severe harm to patients' health status because it damages their physical health, mental state, and social relationships. The development of tuberculosis control strategies requires knowledge about elements that impact the maintenance of the health quality of tuberculosis patients. This study aims to explore the determinants of quality of life in tuberculosis patients qualitatively using thematic analysis techniques with Atlas.ti software in Yogyakarta. Methods: This study used a qualitative design and a case study technique. Patients and TBC program holders from Yogyakarta City's primary healthcare institutions participated in the event. Nine participants were selected using a purposive sampling strategy from individuals who had recently completed treatment and were educated about TBC. In-depth interviews were conducted utilizing an interview guide to gather data. Atlas.ti was used for thematic analysis of the data. This project has been granted ethical approval under license number 369/EA/KEPK-FKM/2024. Results: Most TBC patients have a low quality of life due to physical and psychological disorders, as well as the influence of social stigma. At the same time, the environmental health dimension is in good condition. Determining factors include intrapersonal aspects (knowledge, self-efficacy, motivation), interpersonal aspects (family knowledge and support), and environmental aspects (stigma). Therefore, psychosocial education for patients and their families is crucial for improving quality of life. Conclusion: Tuberculosis patients in Yogyakarta City continue to have a bad quality of life in terms of physical, psychological, and social dimensions. As a result, education is required to promote awareness of TBC among patients and their families, encouraging social support to aid in the healing process, and reducing societal stigma.